Inhibitory Activity of Pineapple fruit (Ananas comosus (L.) Merr.) Meat Extract On Bacteria Streptococcus pyogenes and Proteus mirabilis) - Venny Patricia Syaiful; Wawan Sofwan Z; Ahmad Yani; Puji Hidayati (Jurnal teknologi Kesehatan Borneo, 2020)
Pineapple (Ananas comosus (L.) Merr.) is a fruit that is much in demand by the public. Pineapple contains bromelain enzyme which is believed to kill bacteria. The purpose of this study was to determine the effectiveness of pineapple fruit extracts (Ananas comosus (L.) Merr.) in inhibiting the growth of Streptococcus pyogenes and Proteus mirabilis bacteria. Extraction was carried out using the maceration method using 96% ethanol solvent. This research is an experimental research laboratory. Antimicrobial activity testing is done by the liquid dilution method. The concentration of pineapple (Ananas comosus (L.) Merr.) Extract used was 25 mg/ml, 50 mg/ml, 100 mg/ml, and 200 mg/ml with 10% DMSO as negative control and Chloramphenicol as positive control. The results of this study indicate that the pineapple (Ananas comosus (L.) Merr.) extract can optimally inhibit the growth of Streptococcus pyogenes at a concentration of 50 mg/ml and Proteus mirabilis bacteria at a concentration of 100 mg/mL and 200 mg/mL. Data analysis using the Kruskal-Wallis test showed that there were significant differences (p<0.05) between the concentrations of pineapple (Ananas comosus (L.) Merr.) meat extract in inhibiting the growth of Streptococcus pyogenes and Proteus mirabilis bacteria. Based on the Clinical Laboratory Standards Institute (CLSI, 2018), it can be concluded that the extract of pineapple (Ananas comosus (L.) Merr.) has an antibacterial effect on the bacteria Streptococcus pyogenes and Proteus mirabilis.